Non-aqueous PEDOT:PSS dispersion for improved inverted organic solar cells. Issue 1771 (25th May 2015) - Schumann, Stefan; Elschner, Andreas; Gaiser, Detlef; Lövenich, Wilfried
ABSTRACT: A non-aqueous Poly(3, 4-ethylenedioxythiophene): poly(styrenesulfonic acid) (PEDOT:PSS) dispersion was developed to enable the accommodation of non-polar additives. This additional functionalisation targets selected interface characteristics and results in an improved adhesion of PEDOT:PSS on the photo-active layer. Such mechanical robustness is paramount in inverted organic photovoltaic cells contributing to improved long-term stability.